Fiqh Across Madhhabs: An Alternative to Pesantren Students’ School of Thought Exclusivism in the Post-Truth Era - Muhammad Daud, Zakiul Fuady (Mazahib, 2021)
The schools of thought (madhhabs) within fiqh (Islamic jurisprudence) are one of the ijtihad products explored by qualified Muslim jurists by using a particular methodology to produce Islamic laws, which Muslims then follow. The problem with established madhhabs in Islamic law is when a madhhab follower becomes exclusive and does not want to accept the differences of opinion. Islamic boarding schools (Pesantren) are a medium for developing a deep understanding of Islam and, thus, play an important role in reconstructing the learning of inclusive fiqh. This article aims to explain the meaning of the school of Islamic law exclusivism, solutions, and their impact in the post-truth era. It indicates that the school of Islamic law exclusivism is a form of madhhab fanaticism that only teaches and applies certain madhhab to influence the self-justification of their madhhab and considers those who are different from it are wrong. Hence, this article argues that fiqh-across-madhhab learning is the solution since students are taught all schools of Islamic law, the causes of their differences, and the basis for the arguments used by each eponymous madhhab (Imam). As a result, there will be developed an inclusive understanding in accepting the truth and does not make individuals fanatical and radical in religion.